THE INFLUENCE OF ORGANIC FERTILIZERS AND DEPTH OF SOIL TILLAGE ON GROWTH AND YIELD OF JACK BEAN (Canavalia ensiformis L.) IN GRUMUSOL SOIL MARGINAL LAND - Sri Endah Prasetyowati; Yacobus Sunaryo (Fakultas Pertanian, Universitas Janabadra, 2018)
This study aims are to know the influence of organic fertilizers and the depth of soil tillage on growth and yield of jack bean cultivated in grumusol soil as marginal land. The research was conducted in Playen Village, Yogyakarta Indonesia having latitude 250 m above sea level. The research used 4 x 3 factorial experiment arranged in Randomized Complete Block Design with 3 replications. The first factor is the kinds of organic fertilizers consisting of 4 levels: green manure, cow manure, goat manure, and chicken manure. The second factor is the depth of soil tillage: 15 cm, 30cm, and zero tillage as control. Results of the experiment indicate that the application of glirisidea green manure on the 30 cm depth of soil tillage could result the longest pod length and highest quantity number of leaves. The application of glirisidea green manure could result higher seed yield per ha-1 than that of chicken manure, cow manure as well goat manure. The 15 cm as well as 30 cm depth of soil tillage could result pod number, pod weight and 100 seed weight higher than that of without soil tillage.